Tingkat Adopsi Inovasi Pemasaran Digital pada Pelaku Agribisnis Olahan Limbah Kelapa di Kecamatan Cimerak Kabupaten Pangandaran - Setiawan, Perdi; Setiawan, Iwan; Trimo, Lucyana; Hapsari, Hepi (Universitas Galuh, 2025)
The problem that is the centre of attention in agribusiness development is the effort to accelerate the process of technological innovation, both a new innovation and modification of the agribusiness system, then transform it into the basis for the development of the agribusiness. The purpose of this study was to analyse the level of adoption of digital marketing innovations in coconut waste processed agribusiness actors in Cimerak District, Pangandaran Regency. This research uses quantitative research design with survey method. The analysis used was descriptive analysis and inferential analysis. The results showed that the level of adoption of digital marketing innovations in coconut waste processed agribusiness actors in Cimerak District, Pangandaran Regency was high. In addition, the adoption of digital marketing innovations is also influenced by several variables, namely education, income, and accessibility of agribusiness actors. An increase in these variables will increase the speed of processed coconut waste agribusiness actors in adopting digital marketing innovations.